2017
DOI: 10.3748/wjg.v23.i1.141
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin in patients with non-alcoholic steatohepatitis: A randomized, placebo-controlled trial

Abstract: Sitagliptin does not improve fibrosis score or NAS after 24 wk of therapy. The MRI IDEAL technique may be useful for non-invasive measurement of hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 37 publications
3
100
1
5
Order By: Relevance
“…Comments: The study by Joy et al was limited by its small sample size, and inclusion of patients with relatively mild NASH (baseline NAS score was 3.8 ± 0.8), so it is unclear whether a greater impact would have been found in patients with more‐severe disease. The study by Cui et al was limited by the lack of histological assessment Both studies were placebo‐controlled, double‐blinded studies Both studies involved a short follow‐up duration …”
Section: Modulation Of Ir In Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…Comments: The study by Joy et al was limited by its small sample size, and inclusion of patients with relatively mild NASH (baseline NAS score was 3.8 ± 0.8), so it is unclear whether a greater impact would have been found in patients with more‐severe disease. The study by Cui et al was limited by the lack of histological assessment Both studies were placebo‐controlled, double‐blinded studies Both studies involved a short follow‐up duration …”
Section: Modulation Of Ir In Nafldmentioning
confidence: 99%
“…Both studies were placebo‐controlled, double‐blinded studies Both studies involved a short follow‐up duration …”
Section: Modulation Of Ir In Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…In open‐label prospective trials, sitagliptin has been found to improve plasma aminotransferases, IHTG, and liver histology . But negative results have also been reported with sitagliptin in open‐label studies and in all three placebo‐controlled trials . Negative studies have been also reported with liraglutide, but most have been positive with an improvement in hepatic steatosis (HS) or liver histology .…”
Section: Effect Of Sitagliptin In Nafldmentioning
confidence: 97%
“…We previously reported that the DPP4 inhibitor (DPP4‐I) sitagliptin at a clinically comparable dose successfully ameliorated liver fibrosis by inhibiting platelet‐derived growth factor‐BB‐induced phosphorylation of Smad2/3, p38 mitogen activated protein kinase (MAPK), and extracellular signal‐regulated kinase (ERK)1/2 in As‐HSCs . However, two randomized controlled trials recently showed that sitagliptin alone does not ameliorate liver fibrosis and liver fat in patients with non‐alcoholic fatty liver disease (NAFLD) . Accordingly, OCA + sitagliptin treatment might be beneficial for patients with NASH fibrosis.…”
Section: Introductionmentioning
confidence: 99%